Optimization of Offshore Wind Potential in Gampong Durung Politeknik Pelayaran Malahayati for Electricity in Aceh Besar - Capt. Dedy Kurniadi, M.M; Salfauqi Nurman; Rispa Saeful Mutamar; Syamsul Arifin; Dedi Kurniawan; Harris R Dahlan (Meteor STIP Marunda, 2024)
Utilization of renewable energy especially offshore wind energy increasingly becoming a focus in efforts to diversify energy sources and reduce carbon emissions. Studies This aiming for investigate potential wind off beach in Gampong Durung Politeknik Pelayaran Malahayati Aceh Besar, and proposes an optimization strategy to utilize it in supporting electricity in the region. The research was conducted through a series of methodological steps, including wind pattern mapping, wind speed measurement, historical data analysis, and mathematical modeling. The re-sults of the study show that Village Durung own potential significant winds, with speed and di-rection steady wind throughout year with done speed data measurement wind in Gampong Du-rung on some point. From the results measurement speed wind obtained speed the average wind for 3 months measurement in a way in order are 2.6 m/s, 2.4 m/s, and 2.6 m/s with direction wind most namely northwest. From the results calculation speed wind at 09.00-12.00 which is 463.252 watts, 463.252 watts and 557.7425 watts, then at 13.00-16.00 which is 1115.69 watts, 664.28 watts and 742.355 watts. Based on this analysis, adequate infrastructure planning is also pro-posed to integrate this wind energy with the electricity system in Aceh Besar. By considering economic, environmental and social aspects, this optimization project is expected to be able to provide a positive contribution in meeting the need for sustainable electricity in the region. With Thus, research This suggest that the potential energy wind off beach in Gampong area Durung optimized more Continue. Investment in technology energy wind can give benefit significant economic and environmental for public Aceh Besar coast. The next recommended step is do studies more carry on about design turbine more wind efficient as well as analysis cost For ensure proper implementation useful and sustainable. In conclusion, the research This highlight the huge potential of offshore wind energy as a reliable and sustainable energy source for the people of Aceh Besar.